Validation of the Social Interaction Anxiety Scale in scleroderma: a Scleroderma Patient-centered Intervention Network Cohort study - Gholizadeh, Shadi (2018)
Introduction: Individuals with visible differences due to medical conditions, such as systemic sclerosis (SSc; scleroderma), have reported difficulty navigating social situations because of issues such as staring, invasive questions, and rude comments. Fears or anxiety linked to situations in which a person interacts with others is known as social interaction anxiety. However, there exists no validated measurement tool to examine social interaction anxiety in rheumatologic conditions. Methods: The present study examines the reliability (internal consistency) and validity (structural and convergent) of the Social Interaction Anxiety Scale-6 (SIAS-6) in a sample of 802 individuals with SSc, and compares these psychometric properties across limited and diffuse subtypes of the disease. Multi-group confirmatory factor analysis was used to examine the factor structure of the SIAS-6 in patients with both limited and diffuse SSc. Results: A one-factor structure was found to fit well for individuals with SSc with both limited and diffuse disease. The measure demonstrated strong internal consistency reliability and convergent validity with relevant measures in expected magnitudes and directions. Conclusions: The SIAS-6 is a psychometrically robust measure that can confidently be used in SSc populations to examine social interaction anxiety. Moreover, scores can meaningfully be compared between patients with limited and diffuse disease.